2004
DOI: 10.1111/j.1532-5415.2004.52367.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Adverse Drug Events Among Older Adults in the Ambulatory Setting

Abstract: Prevention efforts to reduce ADEs should be targeted toward older adults with multiple medical conditions or taking multiple medications, nonopioid analgesics, anticoagulants, diuretics, and antiseizure medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
186
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(205 citation statements)
references
References 27 publications
9
186
1
9
Order By: Relevance
“…In the current study antipsychotics had an ADR incidence of 333 per 1000 population and antihypertensive had incidence of 128/1000. This implies that the more drugs with these effects that the elderly patients are exposed to (number and dose), the poorer will be their quality of life and they will be more prone to ADRs, as evident from the results of the current study that those elderly patients who were positive of polypharmacy had 2.3 times more risk of developing ADRs [23].…”
Section: Discussionsupporting
confidence: 57%
“…In the current study antipsychotics had an ADR incidence of 333 per 1000 population and antihypertensive had incidence of 128/1000. This implies that the more drugs with these effects that the elderly patients are exposed to (number and dose), the poorer will be their quality of life and they will be more prone to ADRs, as evident from the results of the current study that those elderly patients who were positive of polypharmacy had 2.3 times more risk of developing ADRs [23].…”
Section: Discussionsupporting
confidence: 57%
“…Na tenta tiva de emprego da gravidade como variável de ajuste, foram extraídas do prontuário informações sobre patologias préexistentes ou diagnosticadas na internação. O Índice de Charlson 21 , método para classificação de gravidade usando dados de comorbidades, vem sendo aplicado para o ajuste de risco e foi demonstrada sua associação com a ocor rência de EAMs em pacientes ambulatoriais com idade igual ou superior a 65 anos 22 . A determinação do Índice de Charlson não é condição indispensável para a aplicação da técnica; entretanto, é uma alternativa possível para o ajuste de risco.…”
Section: Virtudes E Limitaçõesunclassified
“…Adult studies have demonstrated that higher cumulative medication exposures are associated with an increased frequency of ADEs. [7][8][9] Complicating the issue, because the underlying disease processes comprising CCCs are rare and heterogeneous, clinicians may use riskier medications without reliable information to identify, guide, and subsequently monitor drug therapies. 28 Even for routine medications frequently used in the treatment of children with CCCs, such as proton pump inhibitors or antihistamines, there is little evidence to guide best practice in children with CCCs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Many of these characteristics are shared by the pediatric population comprising children with CCCs, who have a chronic or life spanshortening disease process, require lifelong medical care, and often rely on supportive technology (such as tracheostomy, ventilator, or gastrostomy tube) and multiple prescription medications. 11 Children with CCCs may be exposed to multiple concurrent medications in the inpatient 3 and ambulatory settings, potentially increasing their risk of developing ADEs.…”
mentioning
confidence: 99%